2015
DOI: 10.1016/j.theriogenology.2015.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extender, method of thawing, and duration of storage on in vitro fertility measures of frozen–thawed boar sperm

Abstract: Frozen-thawed boar sperm (FTS) has reduced in vitro and in vivo life span compared to liquid semen. Experiments tested whether extenders, thawing procedures, and storage temperatures could extend the fertile life span of FTS. Experiment 1 tested the effect of six extenders on postthaw motility (MOT) and viability (VIA). Straws from boars (n = 6) were thawed, diluted into each extender, and evaluated at 20, 60, and 120 minutes. There was a trend (P = 0.08) for an extender-by-time interaction for MOT and effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Several studies have presented better results of the sperm quality after thawing with the use of high thawing temperatures (70–80 °C) for a relatively short time (8–10 s) [ 8 , 9 , 10 , 32 ]. Similar findings have been observed in the present study, obtaining best results with high temperatures (70 and 90 °C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have presented better results of the sperm quality after thawing with the use of high thawing temperatures (70–80 °C) for a relatively short time (8–10 s) [ 8 , 9 , 10 , 32 ]. Similar findings have been observed in the present study, obtaining best results with high temperatures (70 and 90 °C).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies observed that an increase in the thawing temperature improved the post-thawed motility [ 8 , 9 , 10 , 32 , 35 , 41 , 42 , 43 ], but a limited number of them evaluated the quality of the movement through the kinematic parameters. In general, they observed that an increase in the thawing temperature (60–70 °C) not only improved the total and progressive motility but also increased the velocities (VCL, VSL and VAP) [ 9 , 42 , 43 ], similar trends as those observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, AI is recommended to be performed within 30 min post-thaw [2] because the quality and functionality of boar sperm cannot be maintained for an extended time when it is incubated at 37 • C. However, the distance between where semen is thawed and where the AI is performed demands time flexibility in performing AI and longer temporary storage of post-thaw boar semen. To date, only one study has investigated the effects of post-thaw storage temperature on boar sperm lifespan, indicating that post-thaw storage at 17~26 • C for 2 h facilitates the preparation of frozen-thawed doses [21]. The objective of this study was to evaluate (i) the effect of post-thaw storage at 5 • C (initial temperature of boar semen after thawing at 37 • C for 20 s), 17 • C (conventional semen storage temperature for liquid semen), and 37 • C (constant storage at thawing temperature) on boar sperm survival and (ii) to discover the underlying molecular changes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous accounts of shortened lifespan in frozen-thawed sperm samples have been reported across many species (Cerolini et al, 2001;Katila, 2001;O'Connell et al, 2002;Breininger et al, 2005;Knox et al, 2015;Mari et al, 2015) and have affected the outcome of breeding programs utilising these samples.…”
Section: Introductionmentioning
confidence: 99%